Agents and Peer-to-Peer Computing 5th International Workshop, AP2PC 2006, Hakodate, Japan, May 9, 2006, Revised and Invited Papers - Joseph, Sam; Despotovic, Zoran; Gianluca, Moro; Bergamaschi, Sonia (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the thoroughly refereed post-workshop proceedings of the 5th International Workshop on Agents and Peer-to-Peer Computing, AP2PC 2006, held in Hakodate, Japan, in May 2006, in the context of the 5th International Joint Conference on Autonomous Agents and Multi-Agent Systems, AAMAS 2006. The 10 revised full papers and 6 revised short papers presented together with 1 invited paper were carefully reviewed and selected from 23 submissions; they are fully revised to incorporate reviewers' comments and discussions at the workshop. The volume is organized in topical sections on P2P Infrastructure, agents in P2P, P2P search, and applications.